2019
DOI: 10.1111/tbed.13218
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of equine influenza virus (H3N8) from an equine influenza outbreak in Malaysia in 2015

Abstract: SummaryEquine influenza is a major cause of respiratory infections in horses and can spread rapidly despite the availability of commercial vaccines. In this study, we carried out molecular characterization of Equine Influenza Virus (EIV) isolated from the Malaysian outbreak in 2015 by sequencing of the HA and NA gene segments using Sanger sequencing. The nucleotide and amino acid sequences of HA and NA were compared with representative Florida clade 1 and clade 2 strains using phylogenetic analysis. The Florid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Six (75%) nasal fluid samples from trash service horses that presented characteristic symptoms of Influenza A virus were positive to matrix gene amplification. Although this percentage could be considered high, a recent study showed 96% of EIV detection in nasopharyngeal swabs from equines in Malaysia during an outbreak in 2015 (Toh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Six (75%) nasal fluid samples from trash service horses that presented characteristic symptoms of Influenza A virus were positive to matrix gene amplification. Although this percentage could be considered high, a recent study showed 96% of EIV detection in nasopharyngeal swabs from equines in Malaysia during an outbreak in 2015 (Toh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Six (75%) nasal fluid samples from trash service horses that presented characteristic symptoms of Influenza A virus were positive to matrix gene amplification. Although this percentage could be considered high, a recent study showed 96% of EIV detection in nasopharyngeal swabs from equines in Malaysia during an outbreak in 2015 (Toh et al, 2019). Although there are many viruses that infect the respiratory tract and they could induce similar symptoms, at present, symptoms such as conjunctivitis, runny nose and sneezing has been observed as the main symptoms related to the detection of CIV and EIV (Spickler, 2016;Sigh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%